THE RELATIONSHIP BETWEEN SELF-CONFIDENCE AND WILLINGNESS TO COMMUNICATE IN ARABIC LANGUAGE LEARNING PROCESS - said, Azizah saad; Saleh, Zaenal (JURNAL KONFIKS, 2025)
Low student participation in communication during Arabic language learning often poses a significant barrier to the development of language proficiency. One of the psychological factors believed to influence this participation is self-confidence, which is closely associated with the concept of Willingness to Communicate (WTC). WTC reflects an individual's readiness to initiate communication in a second or foreign language, and it is considered a critical predictor of successful language use in instructional contexts. This study aims to investigate the relationship between self-confidence and WTC in the context of Arabic language learning. Employing a quantitative research design with a survey approach, data were collected through a structured questionnaire administered to university students. The data were then analyzed using correlation techniques to examine the strength and direction of the relationship between the two variables. The findings indicate a significant positive correlation between self-confidence and WTC, suggesting that students with higher self-confidence levels are more likely to engage actively in communication during language learning activities. These results contribute to the field of language education by highlighting the importance of psychological factors in communicative competence. The study underscores the need to incorporate strategies that foster students’ self-confidence as a means to enhance their willingness to communicate, thereby promoting more effective and interactive Arabic language instruction.